PERLINDUNGAN HUKUM BAGI PARA PIHAK TERHADAP PEMALSUAN DOKUMEN JUAL BELI TANAH OLEH PPAT DALAM PERALIHAN HAK ATAS TANAH - Syariffudin, Syariffudin; Slamet Turhamun; Wira Franciska (Journal of Innovation Research and Knowledge, 2025)
Legal protection for the parties against document forgery in land sale and purchase transactions committed by the Land Deed Official (PPAT) in the transfer of land rights constitutes an essential aspect of land law. The issues addressed in this research are: (1) What are the legal consequences of the transfer of land rights through sale and purchase when forgery of documents is committed by a PPAT, and (2) What forms of legal protection are available for the parties against document forgery by a PPAT in the transfer of land rights. This research employs the theory of legal consequences as articulated by Soeroso and the theory of legal protection as developed by Satjipto Rahardjo. The research method applied is normative juridical research, namely legal research based on library studies or secondary data, utilizing sources of primary, secondary, and tertiary legal materials. The research adopts several approaches, including the statutory approach, case approach, analytical approach, and conceptual approach. Legal materials are collected through identification and inventory of positive legal rules, legal literature, books, journals, and other sources of law. The techniques of legal analysis employed include legal interpretation—consisting of grammatical and systematic interpretation—and legal construction, namely analogy construction and legal refinement (rechtsverfijning). The findings reveal that document forgery committed by a PPAT in the transfer of land rights gives rise to serious consequences under civil, criminal, and administrative law. From a civil law perspective, a deed executed on the basis of forged documents is null and void by operation of law, thus the land certificate resulting from such transfer may be revoked by the National Land Agency (BPN) and restored to the rightful owner, even if it disadvantages a bona fide purchaser. From a criminal law perspective, a PPAT proven to have engaged in forgery may be prosecuted under Articles 263, 264, and 266 of the Indonesian Criminal Code (KUHP) with imprisonment as the sanction. From the professional standpoint, a PPAT may be subjected to administrative sanctions, including permanent dismissal. Legal protection for the victims is realized through deed annulment, civil claims for damages, criminal prosecution, and professional supervision by the competent authorities.